Comparative evaluation of retreatability of calcium silicate-based root canal sealers and epoxy resin-based root canal sealers in curved canals-An In-Vitro micro-CT analysis - M V Mavishna; Kondas Vijay Venkatesh (Wolters Kluwer Medknow Publications, 2021)
Objective: To compare and evaluate the retreatability of calcium silicate-based root canal sealers and epoxy resin-based root canal sealers in curved canals using micro-CT scanning. Materials and Methods: Forty-five maxillary molars with curved roots were selected after confirming with the Schneiders test. Teeth were decoronated near the cemento-enamel junction and moderate to severely curved canals were selected for the study using cone-beam computed tomography. All the samples were subjected to pre-operative micro-CT scanning. Cleaning and shaping were done using step-back preparation, obturation was done using lateral compaction technique, and homogeneous obturation was achieved. All the specimens were kept in 10 mL of phosphate buffered-saline solution at a pH of 8.4 for 48 h and transferred to a plastic container containing moistened foam with 10 mL of phosphate- buffered saline solution, and stored at 37 °C with 100% relative humidity for 4 months. Retreatment was performed for all the samples using Protaper universal retreatment files. Micro-CT scanning was performed to compare and evaluate the remaining sealer volume and resultant cracks formed in the root canal after retreatment. Results: The volume of sealer remaining in the root canal and the length of a crack within the groups were analysed using kruskal-Wallis test and among the groups using post-hoc scheffe test showed that more sealer present in the Diaproseal sealer followed by MTA Fillapex and Bioroot RCS and more crack length was seen in Diaproseal sealer followed by MTA Fillapex and no visible cracks were seen in Bioroot RCS, which had statistically significant results with a P value of < 0.05. Conclusion: Within the limitations of the study it was concluded that in-terms of retrievability, Diaproseal sealer was the best among the tested groups followed by MTA Fillapex and Bioroot RCS.